DUTIES OF A NURSE OF HOME CARE IN BELO HORIZONTE, BRAZIL - Alves, Marília; Tavares Araújo, Meiriele; Moreira Santana, Daniela; Loureiro Vieira, Denise (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Objective: To know the process of the nurse work in a service of Home Care in the city of Belo Horizonte-Minas Gerais, Brazil. Methodology: A study of qualitative nature was accomplished in a ﬁrm of Home Care, whose subjects were nurses which work in the management and in the implementation of cares. The data were collected through interviews and submitted to the speech analysis. Results: male nurses assume strategic duty / or activities in the interdisciplinary, work in the relationship with the clientele and in the management of the company. The work is dynamic and ﬂexible, the family exercises a fundamental duty / or activities in the surveillance of the cares rendered by the team and as a partner in the continuity of the same ones. The communication and the professional posture in the relationship with the clientele are essential for the caretakers’ acceptance. Conclusion: The nurse larger autonomy is pointed out, which has shown skilful in the relationships and in the use of light technologies, based on people subjectivity, in the care to the customer in spite of the interference of several factors in the daily work.